Sublethal Injury and Viable but Non-culturable (VBNC) State in Microorganisms During Preservation of Food and Biological Materials by Non-thermal Processes - Schottroff, Felix; Fröhling, Antje; Zunabovic-Pichler, Marija; Krottenthaler, Anna; Schlüter, Oliver; Jäger, Henry (Frontiers in Microbiology, 2018)
The viable but non-culturable (VBNC) state, as well as sublethal injury of microorganisms pose a distinct threat to food safety, as the use of traditional, culture-based microbiological analyses might lead to an underestimation or a misinterpretation of the product’s microbial status and recovery phenomena of microorganisms may occur. For thermal treatments, a large amount of data and experience is available and processes are designed accordingly. In case of innovative inactivation treatments, however, there are still several open points with relevance for the investigation of inactivation mechanisms as well as for the application and validation of the preservation processes. Thus, this paper presents a comprehensive compilation of non-thermal preservation technologies, namely high hydrostatic pressure (HHP), pulsed electric fields (PEF), pulsed light (PL) and ultraviolet (UV) radiation, as well as cold plasma (CP) treatments. The basic technological principles and the cellular and molecular mechanisms of action are described. Based on this, appropriate analytical methods are outlined, i.e. direct viable count, staining, and molecular biological methods, in order to enable the differentiation between viable and dead cells, as well as the possible occurrence of an intermediate state. Finally, further research needs are outlined.